2011
DOI: 10.1007/s11274-011-0684-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and distribution of filamentous heterocystous cyanobacteria isolated from two distinctly located regions in North-Eastern India

Abstract: The diversity of cyanobacteria in the North-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Regardless of their obscure function and our lack of knowledge on how they are maintained and scattered, the widespread dispersion and high conservation ratios of these sequences make them methodologically imperative for DNA fingerprinting, permitting their utilization as an option for taxonomic identification and in diversity studies (Elhai, 2015;Valerio et al, 2009). Today, genomic fingerprints with ERIC, STRR1a, HIP-GC, HIP-CA, HIP-AT, and HIP-TG primers have been generally used for intraspecific comparisons in Cyanobacteria (Akoijam and Singh., 2011;Howard-Azzeh et al, 2014). Analysis of STRRs has been depicted as an amazing asset for taxonomic studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of their obscure function and our lack of knowledge on how they are maintained and scattered, the widespread dispersion and high conservation ratios of these sequences make them methodologically imperative for DNA fingerprinting, permitting their utilization as an option for taxonomic identification and in diversity studies (Elhai, 2015;Valerio et al, 2009). Today, genomic fingerprints with ERIC, STRR1a, HIP-GC, HIP-CA, HIP-AT, and HIP-TG primers have been generally used for intraspecific comparisons in Cyanobacteria (Akoijam and Singh., 2011;Howard-Azzeh et al, 2014). Analysis of STRRs has been depicted as an amazing asset for taxonomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PCR-based techniques largely dependent on DNA polymorphism and fingerprinting of repetitive DNA fragments have been developed (Elhai, 2015). RFLP (Restriction Fragment Length Polymorphism) (Iteman et al, 2002), RAPD (Random Amplification of Polymorphic DNA) (Prabina et al, 2005;Shishir et al, 2015), STRR (Short Tandemly Repeated Repetitive) (Akoijam and Singh, 2011, Valerio et al, 2009, Wilson et al, 2000, HIP1 (Highly Iterated Palindromes) (Neilan et al, 2003, Orcutt et al, 2002, Wilson et al, 2005, Zheng et al, 2002 and ERIC (Enterobacterial Repetitive Interspersed Consensus) (Valério et al, 2005) have been attempted with an overall aim to provide better resolution among closely related species. These repetitive sequences were diagnosed in several cyanobacterial taxa, up to now broadly in heterocystous cyanobacteria (Lyra et al, 2005, Nilsson et al, 2000, Prasanna et al, 2006, Rasmussen and Svenning, 1998, Teaumroong et al, 2002, Wilson et al, 2000, Zheng et al, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Microcystis aeruginosa , Phormidium s p. and Anabaena fl osaquae were the dominant taxa of the Swaroop Sagar Lake (Pandey and Pandey 2002 ). Akoijam and Singh ( 2011 ) reported that Lohtak Lake in Manipur is a reservoir for various kinds of organisms Oscillatoria was represented by maximum number of species. In the lakes at Nagpur, Maharashtra, India, Anabaena , Oscillatoria , Lyngbya , Phormidium and Microcystis were reported as dominant forms (Maske et al 2010 ).…”
Section: Indian Scenariomentioning
confidence: 99%
“…Therefore, the focus of this study was to evaluate the cyanobacterial diversity in the crude-oilcontaminated oil mats and sediments from the Guwahati Refinery and their possible role in bioremediation. On the basis of morphological attributes and patterns of STRR-based rep-PCR DNA fingerprint profiles, cyanobacterial isolates were seen to fall into seven different groups (Rasmussen and Svenning, 1998;Akoijam and Singh, 2011). Rep-PCR generates unique DNA fingerprint profiles for the individual isolates.…”
Section: Strainsmentioning
confidence: 99%